Guided Research-Based Learning in Fostering Research Creativity for Biodegradable Plastic among Prospective Primary School Teachers - Rendi Restiana Sukardi; Fully Rakhmayanti; Nurhidayatulloh Nurhidayatulloh; Alya Rahmadiyani; Mohd Yahya Fadzli Jusoh; Roel Verdadero Avila; Roseleena Anantanukulwong; Nova Kurnia (Universitas Pendidikan Mandalika, 2025)
Indonesia’s position as the world’s second-largest contributor to plastic waste reflects deeply rooted patterns of unsustainable consumption. Addressing this critical issue requires innovative educational strategies to cultivate environmental responsibility and creative problem-solving in future teachers. This study examines how a guided research-based learning (GRBL) model can transform the perceptions of prospective primary school teachers regarding plastic waste management—shifting from conventional 3R (Reduce, Reuse, Recycle) actions to designing environmentally friendly bioplastics. Employing a one-shot case study design, the research was carried out over one semester in a science education course involving 214 fifth-semester students enrolled in a primary teacher education programme. They were divided into 54 groups. Data were collected through observation sheets, student worksheets, and creativity assessment rubrics. The findings suggest that GRBL prompted students to critically engage with sustainability issues by exploring the biodegradability of various natural materials. Most participants selected starch-based substances due to their accessibility and assumed ecological benefits. However, the resulting bioplastic products predominantly exhibited characteristics of modification and imitation rather than originality or innovation. The proportion of students proposing plastic from organic materials increased significantly from 22.2% to 66.7%, with 27.8% suggesting edible straw ideas. While these developments are promising, the ideas lacked originality and were limited to modifications and imitations. This indicates that while GRBL broadened students’ views on waste solutions, their creative outputs remain limited by insufficient scientific exploration and design experience. The study concludes that GRBL has strong potential to foster sustainability-oriented thinking in teacher education, especially when paired with deeper inquiry and iterative practice. These findings highlight the need for science teacher education to embed structured, hands-on research experiences that connect scientific knowledge with real-world environmental issues, preparing future educators to promote both creativity and ecological awareness in the classroom.